2008
DOI: 10.2355/isijinternational.48.1339
|View full text |Cite
|
Sign up to set email alerts
|

New EAF Dust Treatment Process with the Aid of Strong Magnetic Field

Abstract: A new EAF dust treatment process named as "Lime Addition and Magnetic Separation Process (LAMS Process)" has been proposed to recover zinc oxide from the dust and to use solid residue as a flux for steel refining. The LAMS Process consists of the reaction of EAF dust with CaO followed by the adequate crushing and high gradient magnetic separation. The basic principle of this process has been established by revealing the phase equilibria in the CaO-Fe 2 O 3 -ZnO system where Ca 2 Fe 2 O 5 can be in equilibrium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…Based on the heat balance, the input energies required for the LAMS process are essentially simple heating energy up to around 1 000°C and for the rotation of the kiln type reactor. It has also demonstrated that approximately 77 % of ZnFe 2 O 4 in the dust was able to be converted to ZnO and Ca 2 Fe 2 O 5 at 1 100°C at 3 h, 19) which was almost equivalent reaction efficiency for ZnO formation with the Waelz process because the general operating condition of the Waelz process is 6 to 8 h treatment at around 1 200°C. 26) Thus, the input energies of the LAMS process are assumed to be the same as those required in the Waelz process (heavy oil and electric power input).…”
Section: Data and Assumptionsmentioning
confidence: 93%
See 4 more Smart Citations
“…Based on the heat balance, the input energies required for the LAMS process are essentially simple heating energy up to around 1 000°C and for the rotation of the kiln type reactor. It has also demonstrated that approximately 77 % of ZnFe 2 O 4 in the dust was able to be converted to ZnO and Ca 2 Fe 2 O 5 at 1 100°C at 3 h, 19) which was almost equivalent reaction efficiency for ZnO formation with the Waelz process because the general operating condition of the Waelz process is 6 to 8 h treatment at around 1 200°C. 26) Thus, the input energies of the LAMS process are assumed to be the same as those required in the Waelz process (heavy oil and electric power input).…”
Section: Data and Assumptionsmentioning
confidence: 93%
“…The authors 19) have shown that the enthalpy change of Eq. (4) at the boiling point of zinc is approximately Ϫ34.9 kJ/mol (exothermic) while that of Eq.…”
Section: Data and Assumptionsmentioning
confidence: 99%
See 3 more Smart Citations